Formulasi Hair Tonic Ekstrak Etanol Kulit Buah Pepaya (Carica Papaya L.) dan Uji Efektivitas Pertumbuhan Rambut pada Marmut Jantan (Cavia porcellus) - Candani, Mella; Gunawan, Muhammad; Tanjung, Siti Aisyah; Bagas, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Hair for humans has an important role, in addition to protecting the skin from adverse environments, hair also plays an important role in a person's appearance. Losing a lot of hair due to hair loss can cause a lack of self-confidence, disappointment, and frustration, so it must be addressed immediately so as not to worsen the condition that can cause baldness. This study aims to determine whether there is a content of secondary metabolite compounds in fresh herbal medicine, herbal medicine powder and ethanol extract of papaya fruit skin; ethanol extract of papaya fruit skin (Carica papaya L.) can be formulated in the form of hair tonic preparations; whether the difference in concentration of ethanol extract of papaya fruit skin (Carica papaya L.) provides different activities in triggering hair growth in guinea pigs. This research method uses a quantitative approach and is experimental with independent variables, namely papaya fruit skin, herbal medicine, and ethanol extract of papaya fruit skin with concentrations of 10%, 20%, 30%. Research stages: phytochemical screening of fresh papaya fruit peel, powdered simplicia and ethanol extract, hair tonic formulation containing ethanol extract of papaya fruit peel 10%, 20% and 30%, hair tonic evaluation includes: organoleptic, viscosity, stability, pH, irritation, and preference test. And hair growth activity test on male guinea pigs. The results showed that the ethanol extract of papaya fruit peel contains alkaloids, flavonoids, saponins, steroids, and glycosides, can be formulated into hair tonic (EEKP) that meets physical quality requirements. Hair tonic EEKP 30% is the best because it has high hair growth activity, which is an average of 16.375 mm where this EEKP 30% hair tonic has almost the same hair growth activity as the positive control, which is an average of 16.782 mm.